Exposure of Gender Equality through Children Stories for Students of Kranggan Lembur Mandiri Kindergarten, Jatirangga, Bekasi - Hasnini Hasra; Ellita Permata Widjayanti; Rahayu Purbasari; Diyantari (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
This community service activity aims to expose students to understanding the concept of gender and gender  equality in order to minimize oppression, discrimination and bullying that mostly occurs against girls. This  activity also aims to improve students' understanding of the value of character education and positive  attitudes. The partner of this community development are students and teachers of Kranggan Lembur  Mandiri Kindergarten, Jatirangga, Jatisampurna District, Bekasi. This community service activity is  carried out through the method of assisting story reading, designing syllabus of story reading based on  thematic reading, and providing material in the form of children's story books, as well as making children's  story telling videos about gender equality, which can be used for students' independent learning.  Monitoring and evaluation activities are carried out through observation and interviews. This activity helps  improve students' understanding of the role and empowerment of women through education, enrichment of  character and positive attitudes on gender justice (can work together, competence, active, empathize,  problem solving), improve linguistic competence and visual literacy (recognition of colors and images),  and also understanding of cultural literacy through children's stories containing local Indonesian culture  and gender perspective.